PENGUJIAN STRUKTUR MODAL (TEORI PECKING ORDER): ANALISIS EMPIRIS TERHADAP SAHAM di LQ-45 - HERMAN RUSLIM (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
Testing capital structure theory is remain puzzle, most researchers using a static model to explain the dynamic capital structure, however the expectation gap still could not be solved. This research attempts to study the dynamic capital structures which using the effect of profitability, cashflow deficit and long term debt on dynamic capital structure. The measurement of dynamic capital structure using a book value of share price instead of market value to compute the equity of the companies. This research used a sample of the 18 companies in LQ45, which are listed in Indonesia Stock Exchange of the period from 2000 to 2006. The analysis method used in this research was time series analysis with generalized method of moment technique. It was found that the profitability has no significant effect on dynamic capital structures. The research results indicated that the company did not follow pecking order hypotesis.Based on time series analysis, long term debt and cashflow deficit has significant effect on dynamic capital structures. Despite of this, profitability, cash flow deficit and long term debt have a significant effect simultaneously on the dynamic capital structure.